2013
DOI: 10.1007/s13762-013-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization on soil labile carbon fractions of freshwater marsh soil in Northeast China

Abstract: During the past 50 years,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The high C/N in maize stover with a high N level (N300) increased mineralization of LOC, so LOC first increased and then decreased (Tang et al 2020). SR without tillage can improve LOC content (Yang et al 2020b), and a significant positive correlation between N application and LOC has been observed (Huang et al 2014). Tillage practices that influence LOC content and SR improve LOC content, soil nutrient use efficiency and increase ecosystem carbon input (Chen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high C/N in maize stover with a high N level (N300) increased mineralization of LOC, so LOC first increased and then decreased (Tang et al 2020). SR without tillage can improve LOC content (Yang et al 2020b), and a significant positive correlation between N application and LOC has been observed (Huang et al 2014). Tillage practices that influence LOC content and SR improve LOC content, soil nutrient use efficiency and increase ecosystem carbon input (Chen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term application of N fertilizer alone or excess N application will increase soil microbial activity in the short term, thus reducing soil MBC content. Nitrogen input can rapidly stimulate soil microbial activity, improve carbon sequestration in microbial biomass and increase MBC content within a short period (Joergensen & Scheu, 1999;Huang et al 2014). SR combined with an appropriate amount of N can adjust the soil C/N ratio and increase MBC within a particular N range (Murugan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in DOC contents may potentially cause fluctuations in the magnitude of CO 2 emissions (Davidson et al 2000). As a specific fraction of organic C, dissolved organic carbon (DOC) represents an easily degradable and available substrate to microorganisms (Boyer and Groffman 1996;Huang et al 2014). Soil respiration has been revealed to be reliant on C supply (Silva et al 2009;Sevilla-Perea et al 2015).…”
Section: Soil Co 2 Emissionsmentioning
confidence: 99%
“…In the previous studies, Huang et al . () reported that CFs application significantly decreased WSC, but Chaudhary et al . () found that CFs has a positive priming effect on WSC.…”
Section: Discussionmentioning
confidence: 96%
“…However, the response of C and N fractions and their transformations to the application of organic amendments and CFs is still intensively debated. Some studies showed a positive effect of combining organic and inorganic sources of nutrients on increasing soil C and N fractions (Mi et al ., ; Chaudhary et al ., ), whereas others have shown that the combination had no effect (Rudrappa et al ., ; Huang et al ., ). These disparities may result from variations in soil type, cropping system and the quality of the organic pool (Ding et al ., ).…”
Section: Introductionmentioning
confidence: 97%